Soil solution aluminium in disturbed and undisturbed podzolic profiles at two tilt-ploughed forest sites - Tanskanen, N.; Kareinen, T.; Nissinen, A.; Ilvesniemi, H. (Boreal Environment Research Publishing Board, 2024)
Podzolic soil profiles down to the illuvial (B) horizon are inverted on soil surfaces during ploughing of forest soils (as part of forestry practices). As a result, aluminium once immobilized in the horizon may begin to remobilize. In the present study, soil solution Al concentrations in ploughed podzolic profiles were compared with those of the corresponding undisturbed profiles at two forest sites tilt-ploughed 17 (K1) and 31 (K2) years ago. The soil solution was obtained from fresh soil samples, using a centrifugation drainage technique. Aluminium was fractioned to labile monomeric Al, non-labile monomeric Al and acid-soluble Al. Increased concentrations of various Al fractions were observed in the ploughed profiles at both forest sites, especially in the Bs horizons exposed to the soil surface and in the O horizon buried beneath the tilt at site K1. In those horizons where Al had increased, soil solution pH decreased while the concentration of dissolved organic carbon (DOC) increased, suggesting that remobilization of Al occurred in the ploughed profiles.